2018
DOI: 10.48084/etasr.1860
|View full text |Cite
|
Sign up to set email alerts
|

Motivation Factors for Adopting Building Information Modeling (BIM) in Iraq

Abstract: Building information modeling (BIM) is an integrated and comprehensive system including whatever is related to a construction project and its stages. It represents a unified database for all project data through which project documents are available to all stakeholders. This paper evaluates the factors driving the adoption of BIM in Iraqi construction projects in different ministries and adopts quantitative approach to collect data by using a questionnaire survey specially prepared for this purpose which was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
(10 reference statements)
1
10
0
Order By: Relevance
“…Ngowtanasawan [ 109 ] focused on the architectural and engineering design industry in Thailand and divided the BIM adoption factors into technology and people aspects. Hatem et al [ 110 ] identified the motivation factors of BIM implementation in Iraq, such as contracting with international experts. Furthermore, Hatem et al [ 111 ] revealed the barriers of BIM adoption, such as weakness of the government’s efforts, inadequate knowledge about the benefits of BIM, and resistance to change.…”
Section: Discussionmentioning
confidence: 99%
“…Ngowtanasawan [ 109 ] focused on the architectural and engineering design industry in Thailand and divided the BIM adoption factors into technology and people aspects. Hatem et al [ 110 ] identified the motivation factors of BIM implementation in Iraq, such as contracting with international experts. Furthermore, Hatem et al [ 111 ] revealed the barriers of BIM adoption, such as weakness of the government’s efforts, inadequate knowledge about the benefits of BIM, and resistance to change.…”
Section: Discussionmentioning
confidence: 99%
“…use of relevant BIM software, including the learning curve to become competent in the use of BIM software, are not exempt from the list of BIM implementation factors [13,61].…”
Section: Methodsmentioning
confidence: 99%
“…The cost of investment for staff training, software and hardware upgrades and continuous process improvements are also key factors extracted from the literature to support effective BIM implementation. The availability of qualified, skilled and/or experienced personnel for BIM operations and training on the use of relevant BIM software, including the learning curve to become competent in the use of BIM software, are not exempt from the list of BIM implementation factors [13,61].…”
Section: Establishing Bimfd Implementation Factors Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The high energy demand is due to the large buildings (passenger lounges and nonpassenger spaces) equipped with heating and air conditioning systems. Lighting equipment, electricity, and energy needs of the many facilities located in the airport area [27]. Air conditioning systems account for a significant portion of the airport's energy consumption.…”
Section: Literature Reviewmentioning
confidence: 99%